2018
DOI: 10.1089/end.2017.0734
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Review on the Effects of Preoperative 5α-Reductase Inhibitors Treatment in Patients Undergoing Holmium Laser Enucleation of the Prostate: What Do We Know So Far?

Abstract: Overall, 5-ARIs do not seem to affect HoLEP. However, the quality of evidence is still quite poor in comparison with other surgical techniques. Further well-designed studies are required before making any definite recommendations on the use of 5-ARIs in patients undergoing HoLEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Clinical guidelines for BPH [7] describe the definitive indications for surgical managements, considering this a benign disease. The backgrounds of the patients undergoing surgical management are varied, just as the duration of medical treatments, including dutasteride, are also varied [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines for BPH [7] describe the definitive indications for surgical managements, considering this a benign disease. The backgrounds of the patients undergoing surgical management are varied, just as the duration of medical treatments, including dutasteride, are also varied [8].…”
Section: Discussionmentioning
confidence: 99%
“…Trials focused on fibrotic changes of the prostate during 5ARI therapy have confirmed a transforming growth factor-β (TGF-β) concentration increase [30][31]. These fibrotic changes are important because they may cause an increased degree of difficulty in identifying and maintaining the appropriate plane on the surgical capsule of the prostate during transurethral enucleation techniques [22].…”
Section: Agingmentioning
confidence: 99%
“…However, less data is available concerning the effect of pretreatment with finasteride or dutasteride in patients undergoing HoLEP. Initial reports suggest that they are less successful than for traditional transurethral surgery; microvascular density (MVD) decreases significantly but perioperative bleeding does not differ from control groups [21][22][23].…”
mentioning
confidence: 99%
“…Nevertheless, previous studies have demonstrated that 5ARI use did not influence the efficiency of PVP surgery [12][13][14]. It is also possible that 5ARI use may increase the difficulty and decrease the effectiveness of HoLEP surgery, which requires precise identification of the prostate capsule or the interface between the transition and peripheral zones, although conflicting results have been reported regarding the effect of 5ARI use in this setting [7,[15][16][17].…”
Section: Effect Of 5α-reductase Inhibitors On the Efficiency Of Thulium:yttrium-aluminium-garnet (Revolix®) Vaporesection For Treating Bementioning
confidence: 94%